Penerapan Manajemen Cairan Pada Asuhan Keperawatan Anak Dengan Sindrom Nefrotik - Reza Maulita, Firsilia; Dwi Merina, Nuning (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Introduction: Nephrotic syndrome is a collection of symptoms of renal impairment with edema and proteinuria being the main signs. Cases of nephrotic syndrome commonly occur in children. The prevalence of nephrotic syndrome cases in children is 80-90% with no known cause. Nursing problems that arise in this case are related to fluid balance disorders such as excess fluid volume. Fluid management is important in overcoming edema: To analyze nursing care with fluid management measures against edema in children with nephrotic syndrome. Methods: Case study with short nursing care in children. Samples used 1 patient with nephrotic syndrome with fluid management nursing interventions for 3x24 hours in the form of monitoring fluid intake as needed, 24-hour fluid balance, and collaborative diuretic administration. Results: In nursing care for nephrotic syndrome in children with excess fluid volume problems can be resolved with fluid management. Conclusion: Fluid management management effectively reduces symptoms of edema and overcomes hypervolemia in nephrotic syndrome. Recommendations to nurses to conduct careful monitoring of signs and symptoms of nephrotic syndrome, including edema, weight loss, blood pressure, and urine. Intensive monitoring can help early detection of changes in condition.